Proceso de atención de enfermería en paciente pediátrico femenino de 11 años de edad con neumonía. - Montero Ureta, Vania Jomayra (2021)
The following clinical case is based on the analysis of pneumonia diagnosed in an 11-year-old pediatric patient at the Martin Icaza General Hospital in the emergency area. The objective of the research is to establish a care plan applying the Nursing Care Process (PAE) in the patient, through the description of the clinical history, health status, applied tests, identification of functional patterns. The research methodology is based on the Nursing Care Process (PAE) method, a tool that allows the development of care in line with improving the quality of life of the patient and reducing complications of the disease. The findings detected in the investigative process are that the pediatric patient arrived at the hospital facilities with breathing difficulties, which is why nebulizations were carried out for medical indications, in addition tests were carried out to diagnose the disease (Pneumonia not specified). The applied PAE allowed the patient to recover through the nursing professional's care, since the correct intervention was made to improve physical and psychosocial well-being. The study concludes that the participation of the NANDA, NOC and NIC taxonomy shows that favorable results will be obtained when the nursing staff fulfills the role of care with the parameters established in the medical institution.